Microstrip Patch Antenna Design and Analysis for Wireless Communication (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The microstrip antenna required for wideband correspondence ought to be lightweight, ease infabrication and smaller in size. The present situation plan is to create a simple geometrical shaped structure of the microstrip antenna, which would give decent broadband. The paper presents the design analysis of rectangular and square shaped microstrip antenna. Both the antennas used microstrip line for feeding purpose. The square-shaped microstrip antenna is offering wider bandwidth as compared to rectangular microstrip and sufficient return loss. The compact antenna is mean for its operation in X band of frequency. The proposed microstrip antenna is showing a wide bandwidth of 500 MHz with a high return loss of -24 dB. This high bandwidth provides its usefulness in many wideband utilities in X- band.